2005
DOI: 10.1097/01.opx.0000177792.62460.58
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of Aspheric Soft Contact Lenses for the Correction of Low Levels of Astigmatism

Abstract: For small pupil sizes, there is little difference in HCVA and LCVA between various refractive corrections. However, for larger pupils, HCVA and LCVA are superior with TS contact lenses and SC versus AS contact lenses by approximately a half-line or more, which is considered to be clinically significant. Superior vision can be achieved for low astigmatic contact lens wearers using TS rather than AS contact lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 4 publications
1
25
0
1
Order By: Relevance
“…Efron et al [4] suggest five possible reasons that eye care professionals do not routinely correct refractive cylinder of 0.75 DC or less: (1) The small visual improvement is not offset sufficiently by the increased chair time or potential for variability in vision due to axis mislocation. (2) The belief that higher modulus soft contact lenses mask astigmatism. (3) Patient concern over cost.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efron et al [4] suggest five possible reasons that eye care professionals do not routinely correct refractive cylinder of 0.75 DC or less: (1) The small visual improvement is not offset sufficiently by the increased chair time or potential for variability in vision due to axis mislocation. (2) The belief that higher modulus soft contact lenses mask astigmatism. (3) Patient concern over cost.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory is that using aspheric soft contact lenses corrects low amounts of astigmatism. However, Morgan et al [2] found that toric lenses do this much more effectively. Therefore, when astigmatic patients are fit in non-toric soft lenses their refractive error is not fully corrected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have demonstrated that subjects with low levels of astigmatism who were being fitted for contact lenses experienced greater improvements in visual acuity with the use of toric contact lenses compared with either spherical6 or aspheric lenses,7 suggesting that correction of even low levels of astigmatism can positively influence visual outcomes. This study investigated whether improvements in visual performance could be demonstrated by correcting low levels of postoperative astigmatism using full correction, instead of spherical equivalent correction, in pseudophakic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…(9) Visual acuity with toric lenses is better than with spherical or aspheric lenses, but initially lens quality and stability was a problem. Nowadays, improved lens designs and the availability of disposable toric contact lenses have resulted in improved health benefits and adaptation (10) Well-fitted hydrogel toric lenses can provide visual acuity and visual performance equivalent to that of spherical RGP lenses. (9) All the literature agrees that the best way to fit a soft lens is by considering the response to the trial lens fitting.…”
Section: Soft Contact Lensesmentioning
confidence: 99%